Organización perceptiva y escritura cursiva en primer grado de primaria de tres instituciones educativas del Callao - Vizcarra Figueroa, Cristina del Rosario (2012)
This descriptive correlational research aims to determine the relationship between perceptual organization and quality calligraphic cursive writing of the first grade primary students of three public schools in Callao. The sample were 112 students (57 girls and 55 boys) aged 6 years. To measure perceptual organization the Santucci (1978) test of perceptual organization was applied, and the Condemarin and Chadwick exploratory writing test (1982) was administerd to measure quality calligraphic cursive writing. The result showed that there is a relationship between perceptual organization and cursive writing in its 3 dimensions: normal speedy of execution, rapid speed of execution and quality of copy. It was concluded that the greater perceptual organization, the better performance in the quality calligraphic cursive writing.